"Сусіди-вороги” чи партнери спільного минулого: образ кримських татар в українських підручниках з історії - Батуріна, С. (Історіографічні дослідження в Україні, 2020)
За відносно невеликий проміжок часу схема минулого кримсько-татарського народу в структурі шкільного курсу української історії
зазнала суттєвих змін. Вони були передусім зумовлені політичними
подіями 2014 р. Українські підручники, за часом їх створення, можна
розділити на дві категорії. В одній із них, представленій виданнями
переважно до 2016 р., існує традиція вітчизняної і радянської історії
з яскраво вираженим фронтирним дискурсом, згідно з яким степовий
світ, представниками якого були й кримські татари, вважався
чужим, ворожим і деструктивним. У національному наративі він
виступав виключно в ролі антагоніста. Причому кримська тематика
у підручниках ніколи не була самостійною, а висвітлювалася
ситуативно задля підкреслення трагічних чи героїчних сторінок
українського минулого. У новому поколінні підручників зроблено спробу
трактування історії кримсько-татарського народу як самостійної
категорії, розуміння непростого досвіду українсько-татарського
співіснування на спільній території. To conduct this study 55 ukrainian history textbooks were included in
the analysis. Chronologically, they cover material from the Middle Ages to
the present. Are the Tatars represented as a part of the common past, or is
their history presented separately from the Ukrainian one? Is their past in
the Ukrainian vision a story of an enemy, a neighbor, a partner of a
common past? What topics, periods of the historical path of the Crimean
Tatars, their states interested the authors of textbooks? How do these
chronological periods relate to the relevant events in Ukrainian history?
What prevails in textbooks – the history of the people or the state? What are
the features of the representation of the history of the Crimean Tatars
depending on the time of writing the textbook? In a relatively short period
of time, the scheme of the past of the Crimean Tatar people in the structure
of the school course of Ukrainian history has undergone significant
changes. They were primarily due to the political events of 2014. Ukrainian
textbooks can be divided into two time categories. In one of them, presented
by publications mainly until 2016, there is a tradition of national and Soviet
history with a pronounced frontier discourse, according to which the steppe
world, which was represented by the Crimean Tatars, was considered alien,
hostile and destructive. In the national narrative, they acted exclusively as
an antagonist. Moreover, the Crimean theme in the textbooks was never
independent, but was covered situationally to emphasize the tragic or
heroic pages of the Ukrainian past. In the new generation of textbooks, an
attempt is made to interpret the history of the Crimean Tatar people as an
independent category, to understand the difficult experience of Ukrainian-
Tatar coexistence on a common territory.